Bioactive Compounds Investigation and Antioxidant Activities in Extracts and Fractions of Tamarindus Indica (Aradib) From Sudan - Alhasien Ahmed, Mona; Mohammed , Abuelgasim Abbaker; Ishag, Khogali Elnur (Indonesian Journal of Chemical Analysis (IJCA), 2024)
Tamarindus indica is commonly used interest in Sudan for edible plant and medicinal use. This study aimed to determine bioactive compounds, and antioxidant activities in extracts and fractions of Tamarindus indica pulp grown in Sudan. The powdered plant was extracted with ethanol, ethyl acetate, and acetone using an ultrasonic technique. The residue of the ethanol extract was fractionated using successive solvents. The extracts and fractions were determined for their phenolics, flavonoids, and tannins contents, and analyzed bioactive compounds by Gas Chromatography-Mass Spectrophotometer, and also evaluate their antioxidant activities using the 2, 2-diphenyl-1-picryl-hydrazyl, reducing power and hydrogen peroxide scavenging methods. The results show that the total phenolics, total flavonoids, and total tannins levels were significantly higher in the ethyl acetate fraction than in other extracts and fractions. GC-MS analyses of extracts and fractions showed a variety of bioactive compounds such as Hexadecanoic acid, Stigmasterol, Maltol, Sitosterol, Vitamin E, Allose, Tartaric acid, and Vaccenic acid. All the extracts and fractions exhibited good antioxidant activities. The extracts and fractions of Tamarindus indica pulp are sources of natural antioxidants and other bioactive compounds, which are beneficial effects on human health and the possibility of application in the pharmaceutical industry.